Analisis Evaluasi Pelaksanaan Proyek Bendungan Sibiru Biru dengan Metode CPM (Critical Path Method) di PT. PP Andesmont KSO - Wiratama, Yuda; Sutrisno, Sutrisno; Polewangi, Yudi Daeng (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
A construction project is a form of activity that lasts for a limited period of time, with certain resources, where the process requires a technique to be used, namely management, planning, scheduling to control. It is not uncommon for construction projects to experience delays in completing the completion time, so that many losses occur, especially in time and costs. With this fierce competition, timely completion of projects is a top priority for construction companies. The purpose of this study is to evaluate the time of scheduling for project completion using the CPM method on the grounds that the shape of the network or network planning can be identified along with the activities that are on the critical path, and can also be known for a more efficient time in carrying out this project. Based on network planning analysis using the CPM method, a series of work activities were obtained that were included in the critical path and the evaluation results showed that the project could be completed in 668 days and then accelerated using the CPM method again, so the project could be accelerated to 545 days, so that the percentage of time efficiency after crashing is 18.42%, with a total cost of IDR 176,557,549,469.00 with a percentage of cost efficiency after crashing is 0.03%.